2020
DOI: 10.18502/ijaai.v18i6.2173
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Dietary Inflammatory Index, Pulmonary Functions and Asthma Control in Asthmatics

Abstract: This cross-sectional study evaluates the relationship of the dietary inflammatory index (DII), a novel tool developed to measure the inflammatory capacity of a diet, with pulmonary functions and asthma control test (ACT) scores in asthmatic individuals. The study included 120 patients who were diagnosed with asthma for at least one year.  The anthropometric measurements, one-day long nutrition uptake records, pulmonary function tests, and ACT scores of the respondents were recorded and compared according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…Our results showed that there were positive significant relationships between DII and CRP, hospitalization, neutrophil, WBC, NLR, and disease severity. Similar to our results, various observational studies have reported that higher DII increases the risk of lung-related inflammatory conditions such as asthma (36,37) and COVID-19 (13,38). Similarly, studies conducted on other health conditions have reported positive associations between CRP and immune system biomarkers with DII values (39, 40).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results showed that there were positive significant relationships between DII and CRP, hospitalization, neutrophil, WBC, NLR, and disease severity. Similar to our results, various observational studies have reported that higher DII increases the risk of lung-related inflammatory conditions such as asthma (36,37) and COVID-19 (13,38). Similarly, studies conducted on other health conditions have reported positive associations between CRP and immune system biomarkers with DII values (39, 40).…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that higher intakes of anti-inflammatory micro-nutrients (vitamins A, D, and E as fat-soluble vitamins, vitamins C, B1, B2, B3, B6, and B9 as water-soluble vitamins, betacarotene, iron, magnesium, zinc, and selenium) led to the lower DII and E-DII values. Similarly, Özbey et al reported that intakes of vitamins A, E, and C had a negative relationship with DII values (36). Kim et al also demonstrated that dietary vitamins A, D, E, C, B1, B2, B3, B6, and B9, and beta-carotene, zinc, selenium, and magnesium were negatively associated with DII values (45).…”
Section: Discussionmentioning
confidence: 92%
“…These results are not consistent with our findings because the authors did not consider DII in their analyses; moreover, the outcome of interest was asthma exacerbations, which could be considered as a component of asthma burden. More recently, a cross‐sectional study on Turkish adults with asthma showed a significant inverse correlation between DII computed on a 24‐hour recall questionnaire and asthma control 36 . Despite relevant differences in the study population and design, these results are in line with our findings, highlighting the adverse effect of a pro‐inflammatory diet on asthma control, which can be considered a component for asthma burden.…”
Section: Discussionsupporting
confidence: 90%
“…More recently, a cross-sectional study on Turkish adults with asthma showed a significant inverse correlation between DII computed on a 24-hour recall questionnaire and asthma control. 36 Despite relevant differences in the study population and design, these results are in line with our findings, highlighting the adverse effect of a pro-inflammatory diet on asthma control, which can be considered a component for asthma burden.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the impact of an overall healthy diet as a disease modifier, a healthier diet was associated in our study with a lower risk of uncontrolled asthma but the association did not reach statistical significance. Five studies have been published so far, all among middle-aged adults and overall, they reported mixed findings as follows: three studies reported an association between an overall healthy diet and lower uncontrolled asthma [ 48 50 ], one reported no association [ 51 ], and one reported a borderline significant association in women [ 18 ]. Published studies are very heterogeneous in term of tools used to evaluate asthma control as follows: two used the ACT [ 18 , 50 ] and three used the asthma control questionnaire (ACQ) [ 48 , 49 , 51 ]; in terms of tools used to collect dietary data, three used 24-h dietary records [ 18 , 48 , 50 ], and two used a FFQ [ 49 , 51 ]; and in terms of tools used to estimate the overall diet, one used the Dietary Approaches to Stop Hypertension (DASH) score [ 48 ], one used the DII [ 50 ], two used the Mediterranean diet score [ 49 , 51 ], and one used the AHEI-2010 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%